2017
DOI: 10.1080/00016489.2017.1294763
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glass ionomer cement on facial nerve: a clinical and histopathologic evaluation

Abstract: Bone cement directly applied on the nerve causes foreign body reaction increased inflammation and granulation tissue. Nonetheless it does not lead to a permanent facial nerve dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…To prevent such incidence gelfoam is placed over the stapes footplate and the facial nerve during the process of application. [11,12] Another advantage of bone cement that it got no interference regarding graft take rate. [13] in our cases we used gelfoam as supporting material when tympanic membrane grafting is done, this gives protection against contact between the tympanic membrane and the bone cement.…”
Section: Discussionmentioning
confidence: 99%
“…To prevent such incidence gelfoam is placed over the stapes footplate and the facial nerve during the process of application. [11,12] Another advantage of bone cement that it got no interference regarding graft take rate. [13] in our cases we used gelfoam as supporting material when tympanic membrane grafting is done, this gives protection against contact between the tympanic membrane and the bone cement.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the potential neurotoxicity of glass ionomeric cement, contact with neural structures, perilymph or dura should be avoided 4 , 10 . In the event of contamination, bone cement should be aspirated instantly and multiple attempts at aspiration and irrigation of the middle-ear cavity with serum is essential to extract the bone cement 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Although bone cement has a neurotoxic effect by increasing inflammation and the formation of granulation tissue, Kum and Kulacoglu reported that it does not give rise to permanent dysfunction of facial nerves 10 . The heat produced in the preparation of bone cement is perhaps another disadvantage of bone cement.…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported that GIC caused foreign body reaction, increased inflammation, and granulation tissue formation around the nerve, but it did not lead to a permanent facial nerve dysfunction. 21 In case of any contamination of GIC with neural structures, GIC should be suctioned carefully and tympanic cavity should be irrigated with sterile saline. In our study, we did not observe any serious complication associated with GIC.…”
Section: Discussionmentioning
confidence: 99%